The yield of multi-rowed barley (var. pallidum) in the arid steppe zone - G. V. Kozubovskaya; V. I. Balakshina (Труды по прикладной ботанике, генетике и селекции)
Background. Cultivated in the arid steppe zone of Volgograd Province is mainly two-rowed spring barley of the varieties nutans and medicum (Hordeum vulgare L. subsp. distichon (L.) Koern. var. nutans Schuebl. and H. vulgare L. subsp. distichon (L.) Koern. var. medicum Koern.). The areas under multi-rowed spring barley, with higher yield potential, are minimal. The aim of this work was to study multi-row spring barleys of the variety pallidum (H. vulgare L. subsp. vulgare var. pallidum Ser.) of various origins in the arid steppe environment. Materials and methods. The research was conducted in the arid steppe zone of Volgograd Province, with its light-chestnut heavy loamy soils, on the experimental field of the Lower Volga Research Institute of Agriculture. The nursery was set up according to the standard technique, and 120 multi-rowed spring barley accessions representing the pallidum variety from 11 countries were selected for the research. The commercialized two-rowed barley cultivar ‘Donetsky 8’ of the medicum variety was chosen as a reference. Results and conclusions. In the arid steppe environment of Volgograd Province, on light-chestnut heavy loamy soils, with the precipitation amount of 51.6–168.1 mm during vegetation and the hydrothermal coefficient (HTC) of 0.5–0.83, the productivity of all multi-rowed spring barley accessions of the pallidum variety was lower than that of the reference. Under dryer conditions (HTC = 0.5), the accessions from Tajikistan and Turkmenistan demonstrated good results, while in a wetter year (HTC = 0.83), those from Kyrgyzstan, Peru, Turkmenistan and Uzbekistan proved better. During all the years of experimenting, the accessions from Mexico and Bolivia were producing 1.2–1.5 times lower yields than the average for the collection. The accessions from Egypt had the highest economic efficiency ratio (36.9%–41.4%).